THE APPLICATION OF THE ARAS METHOD IN EVALUATING THE TOP GRADUATING STUDENTS - Thamrin, Musdalifa (Nusantara Hasana Journal, 2026)
This study aims to design and develop a decision support system for identifying the top graduating students using the Additive Ratio Assessment (ARAS) method at STMIK Profesional Makassar. This system was developed to facilitate the objective evaluation of students based on several criteria, namely GPA, TOEFL scores, academic achievements, and organizational involvement. The ARAS method was used because it is capable of performing an alternative ranking process based on predetermined criteria values and weights. Data collection was conducted through interviews, observations, and literature reviews. The system was built using the PHP programming language and a MySQL database. The results of the study indicate that the application of the ARAS method can assist the university in identifying the top students more effectively, quickly, and accurately based on the results of optimization calculations and alternative student rankings.